EFISIENSI PELAKSANAAN TEBU RAKYAT INTENSIFIKASI (TRI) SECARA KOLEKTIF DI KECAMATAN PRAMBON KABUPATEN SIDOARJO - Priyanto, Eko (Berkala Ilmiah AGRIDEVINA, 2014)
Socioeconomic motivation that push member of farmer group for remain to execute management TRI in collective. Social of motivation have the shape of :  Generally member of farmer group shy at execute TRI by it self; Irrigating TRI in rotation; Generally  member of farmer group have job outside TRI; Existence of system glebagan. Economy of motivation have the shape of : Generally farmer haves narrow/tight farm (< 0,5 Ha); Farmer have earnings outside TRI; Expense is helped by Sugar mill; Farmer have profitable Sharing holder TRI. Management Mechanism TRI in collective beginning with Determination of glebagan; Forming of farmer group; Credit Proffering; Execution of farm sugar cane; Cut away transport sugar cane; Sharing holder Determination; At last Liquefaction of DO (Delivery Order).